Transformational Leadership Model & Its Philosophical Applications (International Journal of Innovative Research in Engineering & Management, 2022)
It is the process through which a leader,  by virtue of a strong emotional connection with his or her  supporters & a shared commitment to a larger moral  purpose, enables community or organizational  achievement that exceeds expectations. It is purpose of this  study to investigate origins & development of phrase transformational headship. An investigation of many indicators & assessment techniques that have created to  better understand how transformational headship is  implemented & how it might be produced & then executed.  This article provides a thorough overview of broad variety  of settings in which transformational headship has  experimentally examined, along with a complete  evaluation of most widely researched theoretical  connections that have statistically assessed. A discussion  of some of difficulties that have levelled at  transformational headship, along with how domain might  be enhanced more efficiently.
Keywords: Culture; Development; Headship; ransformation Leader; Transformational Headship